Rational Design of Micro-RNA-like Bifunctional siRNAs Targeting HIV and the HIV Coreceptor CCR5 - Ehsani, Ali (Nature Publishing Group, 2010)
Small-interfering RNAs (siRNAs) and micro-RNAs (miRNAs) are distinguished by their modes of action. SiRNAs serve as guides for sequence-specific cleavage of complementary mRNAs and the targets can be in coding or noncoding regions of the target transcripts. MiRNAs inhibit translation via partially complementary base-pairing to 3′ untranslated regions (UTRs) and are generally ineffective when targeting coding regions of a transcript. In this study, we deliberately designed siRNAs that simultaneously direct cleavage and translational suppression of HIV RNAs, or cleavage of the mRNA encoding the HIV coreceptor CCR5 and suppression of translation of HIV. These bifunctional siRNAs trigger inhibition of HIV infection and replication in cell culture. The design principles have wide applications throughout the genome, as about 90% of genes harbor sites that make the design of bifunctional siRNAs possible.